Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4018/ijepr.2016010101
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Analysis for the Study of Relationships between the Emotional Responses of Urban Walkers to Urban Spaces

Abstract: The described study aims to find correlations between urban spatial configurations and human emotions. To this end, the authors measured people's emotions while they walk along a path in an urban area using an instrument that measures skin conductance and skin temperature. The corresponding locations of the test persons were measured recorded by using a GPS-tracker (n=13). The results are interpreted and categorized as measures for positive and negative emotional arousal. To evaluate the technical and methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…As such, our brain and nervous system responds distinctly to different spatial settings (e.g., urban and greenery [45]). This is similar evident in Hijazi et al (2016) [46], who conducted a small-sample study in which participants wore a skin conductance wristband while roaming freely in an environment. They concluded that participants physiological response was linked to changes of a spatial scene, e.g., street intersections.…”
Section: Psychological Potential Of Urban Formsupporting
confidence: 79%
“…As such, our brain and nervous system responds distinctly to different spatial settings (e.g., urban and greenery [45]). This is similar evident in Hijazi et al (2016) [46], who conducted a small-sample study in which participants wore a skin conductance wristband while roaming freely in an environment. They concluded that participants physiological response was linked to changes of a spatial scene, e.g., street intersections.…”
Section: Psychological Potential Of Urban Formsupporting
confidence: 79%
“…Hence the need for a 'vitalist stance' and the development of experiments in "posthuman health geographies" (Andrews 2018). Fourth, in contrast to studies that infer emotional states from simple physiological data (Bergner et al 2013;Hijazi et al 2016;Zeile et al 2009), we have argued for a contextualization and triangulation of these measurements with environmental and ethnographic data to produce a truly ecological interpretation of urban experience in mental health research.…”
Section: Resultsmentioning
confidence: 92%
“…To our knowledge, EDA activity has not been put to use in situ in urban environments for the monitoring psychophysiological arousal of people living with a diagnosis of psychosis. However, there is indeed a growing body of work assessing EDA with healthy participants in real world settings within cities (Alajmi et al 2013;Bergner et al 2013;El Mawass and Kanjo 2013;Hijazi et al 2016;Hogertz 2010;Kim and Fesenmaier 2015;Li et al 2016;Zeile et al 2015). Furthermore, EDA has been used in laboratory studies as a psychophysiological indicator of arousal in participants living with a diagnosis of psychosis (Lincoln et al 2015), and it has been used in situ to detect autonomic signature of illness (Cella et al 2018).…”
Section: The 'Bio' In Urban Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…This is explored in an earlier study [5], which evaluates the relationships between urban spatial configurations along a select street network and subjective impressions through survey responses. Another study [6] follows a similar methodology but also includes physiological response data from participants using biofeedback wristbands.…”
Section: Related Workmentioning
confidence: 99%